Field measurement analysis of the influence of simultaneous construction of river channel and bridge on existing double shield tunnels - Wenhui Yang; Dingwen Zhang; Anhui Wang (Underground Space, 2022)
This study presents the construction of a river channel and a bridge adjacent to existing metro tunnels in Changzhou. The influence of simultaneous construction on these existing tunnels was investigated via 3D numerical modelling to predict tunnel deformation before construction. Then, a targeted protection scheme was developed according to the obtained numerical results. The full construction period field monitoring scheme can monitor tunnel responses during construction. Subsequently, the safety of the tunnel structures was evaluated according to the monitoring results, and the evolution of tunnel deformations was analysed. The analytical results can help to clarify the influence characteristics of different construction stages, verify the effect of the proposed protection scheme, and determine the disturbance mechanism of short-distance pile construction. According to the results, the tunnel deformation mainly occurred during pile construction and river channel excavation, and the tunnel vertical displacement and convergence were mainly affected by the construction. The anti-floating scheme of the partition excavation and casting effectively controlled the tunnel heave with an alarm value of approximately 6 mm. The penetration of the short-distance casing resulted in a tunnel deformation. The main construction influence area of the casing pile was within 6D (D is the pile diameter).